Local Production and Storage in Positive Energy Districts: The Energy Sharing Perspective - Fichera, Alberto; Pluchino, Alessandro; Volpe, Rosaria (Frontiers in Sustainable Cities, 2021)
In response to the Positive Energy District transition, this paper proposes an energy tool for the modeling of energy sharing configurations among buildings equipped with energy production systems and distributive storages. The model is targeted for urban planners and energy policymakers and gives insights into the role of buildings in fostering the achievement of net-zero energy balances in districts when virtual or physical peer-to-peer configurations are established in the area. A real urban district is considered as a case study and the energy performances are measured against properly defined Key Performance Indicators. Results confirm the strategic role played by energy sharing among buildings in achieving self-sufficient and carbon-neutral areas. In particular, the insertion of storages allows not only for higher self-sufficiency of the area (by facilitating the coupling of production and demand) but also for higher distribution rates among buildings. However, photovoltaic diffusion and storages should be appropriately balanced since it has been observed that at increasing the number of production and storage systems, the distribution is reduced in favor of autonomy, thus limiting the usefulness of an interconnected local distribution grid.